Nanoemulsions in Skin Cancer Therapy: A Promising Frontier - Basu, Biswajit; Dutta, Ayon; Ash, Dipanjana; Prajapati, Bhupendra (Current Pharmaceutical Biotechnology, 2025)
Skin cancer, a global burden for particularly white people, is classified as various histopathological types, including malignant melanoma, basal and squamous cell carcinoma, on the basis of affected different skin layers. Clinical adjuvant therapy (electro-chemotherapy, radio-and immuno therapy), surgical techniques (Cryosurgery, laser treatment, dermabrasion, Moh's micrographic surgery), photodynamic treatment and theranostic approaches are confined only for the treatment of serious health issues. Therefore, nanotechnology based approaches, especially nanoemulsion, a non-spontaneous, transparent or translucent, kinetically stable nano-structured (1-1000nm) colloidal dispersion (comprised of oil, water and surfactant/co-surfactant), are being popularised as a potential topical nanocarrier to deliver BCS class II and IV anti-neoplastic drugs attributing to its capacity for both active and passive tumor targeting in controlled or sustained manner and improving bioavailability via enhancing permeability-retention effect with minimal adverse effects. Numerous research on nanoemulsion for the treatment of both melanoma and non-melanoma skin cancer is only limited to preclinical stages as several physiological variables reduce the effectiveness of nanoemulsion via restricting topical penetration.
Keywords: Colloidal dispersion